Is the Fastest Mri a Hologram? - Raff-Biggemann, U (Blackwell Publishing Inc., 2014)
Real-time MR imaging might exert a profound influence on neuroscience in the future by enabling the direct visualization of neuronal interactions. At this time, however, all practical embodiments of MRI require at least some degree of gradient encoding, and this in turn sets a lower limit of about 100 ms for volume acquisition. A novel formulation of MRI is proposed here which is given the acronym ULTRA (Unlimited Trains of Radio Acquisitions). In the preferred embodiment ULTRA is completely free of gradient reversals, which allows for signal acquisition from the entire object volume simultaneously. This permits a rate of signal acquisition that is increased hundreds of times compared with existing techniques, with full 3-D imaging in as little as one millisecond. The proposed detector now resembles a holographic recording. © 2014 by the American Society of Neuroimaging.